An empirical modelling framework for forecasting freight transportation - Güler, Hakan (Transport, 2014)
This paper presents a framework which includes empirical modelling methods to estimate freight transportation between defined zones. In this method, observed origin and destination matrices for each type of freight are constituted based on the link counts and the roadside truck survey data. The gravity method is selected to estimate origin and destination matrices by using observed link flows, gross domestic product by provinces and interzonal distances. Advanced statistical techniques and regression analyses are used to estimate the coefficients of the gravity method. The final freight transportation matrix is calibrated with the link flows data by using iterative techniques. The developed method was applied to find the origin and destination matrix of the total freight transportation in Turkey and successful results were obtained.